2017
DOI: 10.26651/2017-42-1-1103
|View full text |Cite
|
Sign up to set email alerts
|

Herbicide activity of natural compounds from Baccharis spp Herbicidal activity of natural compounds from Baccharis spp. on the germination and seedlings growth of Lactuca sativa and Bidens pilosa

Abstract: CITATIONS 0 READS 401 3 authors: Some of the authors of this publication are also working on these related projects: Effect of PGPG on alleviating salinity stress in maize View project Characterization of Streptomyces spp. isolates from Fabaceae rhizosphere as Plant Growth Promoting Rhizobacteria in soybean [Glycine max (L.) Merrill] View project ABSTRACTWe evaluated the effects of aqueous and ethanolic extracts from 3-Baccharis species (B. dentata, B. uncinella and B. anomala) on the germination and seedlings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Coumarins are a large group of secondary metabolites derived from phenolic compounds, are produced mainly by higher plants, and may also occur in some fungi and bacteria [4]. There are reports about the bioactivity of coumarins that indicate these substances are a potential alternative to commercial herbicides, which is based on inhibiting germination and initial growth and development, as well as blocking mitosis in innumerable biotests [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Coumarins are a large group of secondary metabolites derived from phenolic compounds, are produced mainly by higher plants, and may also occur in some fungi and bacteria [4]. There are reports about the bioactivity of coumarins that indicate these substances are a potential alternative to commercial herbicides, which is based on inhibiting germination and initial growth and development, as well as blocking mitosis in innumerable biotests [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…These compounds were also identified in the work of Rezende et al [63] and Sousa et al [64] in B. dracunculifolia extract. Catechin (6.06 mg/L) is commonly found in species of the genus Baccharis ; e.g., B. uncinella , B. dentata , and B. anomala [65]. The presence of these bioactive compounds identified by HPLC analysis indicate the resistance of the microparticles to the temperature conditions employed in the atomization process during spray-drying.…”
Section: Resultsmentioning
confidence: 99%
“…Corsato et al (2008) observed that the extract of Lupinus albus affected the germination of B. pilosa at the lowest concentration (20%), even managing to completely inhibit the germination of the species at concentrations of 80 and 100%, which contrasts with what was obtained in this experiment, probably due to the amount of the concentrations and the species of Lupinus used in their research. Various studies showed that B. pilosa germination rate is strongly affected by other allelopathic substances as essential oils, phenolic, polyphenols and terpenoids (Dias et al, 2017;Barbosa et al, 2018;Ferreira et al, 2020).…”
Section: Germination Curves By Speciesmentioning
confidence: 99%